In situ biogas upgrading via cathodic biohydrogen using mitigated ammonia nitrogen during the anaerobic digestion of Taihu blue algae in an integrated bioelectrochemical system (BES) - Wu, H.; Wang, H.; Zhang, Y.; Antonopoulou, G.; Ntaikou, I.; Lyberatos, G.; Yan, Q.
Biohydrogen using migrated ammonia as nitrogen source, and biogas upgrading with hydrogen collected at biocathode in an integrated bioelectrochemical system (BES)were investigated, during the anaerobic digestion of Taihu blue algae. Under an applied voltage of 0.4 V, biohydrogen (202.87 mL)reached 2.34 and 2.90 times than groups with applied voltage of 0 V and 0.8 V, respectively. Moreover, biohydrogen of the group with 1000 mg/L initial ammonia addition (524.16 mL)reached 1.53 times than that the of the control. With 0.25 bar of H2 injected at the beginning (R1), highest methane production (286.62)mL and content (75.73 percent)were obtained. Comparing to other groups, not only microbial genus responsible for both aceticlastic and hydrogenotrophic methanogens of the group R1 were apparently enriched, but key enzymes related to methane production also acquired better abundances. Therefore, it's promising to conduct the ammonia alleviating, hydrogen producing and biogas upgrading simultaneously using BES.
Keywords: TAIHU BLUE ALGAE; BES; AMMONIA MITIGATION; CATHODIC BIOHYDROGEN; BIOGAS UPGRADING